2007
DOI: 10.2214/ajr.06.1208
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic MRI of the Knee with 3D Fast Spin-Echo Extended Echo-Train Acquisition (XETA): Initial Experience

Abstract: Three-dimensional FSE XETA acquires high-resolution (approximately 0.7 mm) isotropic data with intermediate and T2-weighting that may be reformatted in arbitrary planes. Three-dimensional FSE XETA is a promising technique for MRI of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
122
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 180 publications
(123 citation statements)
references
References 28 publications
0
122
0
1
Order By: Relevance
“…To improve scanning efficiency and generate a large isotropic image volume in feasible time, Cube features autocalibrating reconstruction for Cartesian imaging (ARC), a 2 Daccelerated autocalibrating parallel imaging reconstruction method [8,9]. Cube has already been evaluated for imaging of the knee and ankle, yielding positive results [10,11]. Moreover, Cube FLAIR was shown to produce almost no CSF flow artifacts when applied in brain imaging [12].…”
mentioning
confidence: 99%
“…To improve scanning efficiency and generate a large isotropic image volume in feasible time, Cube features autocalibrating reconstruction for Cartesian imaging (ARC), a 2 Daccelerated autocalibrating parallel imaging reconstruction method [8,9]. Cube has already been evaluated for imaging of the knee and ankle, yielding positive results [10,11]. Moreover, Cube FLAIR was shown to produce almost no CSF flow artifacts when applied in brain imaging [12].…”
mentioning
confidence: 99%
“…When applied to the temporal bone pathologies, this 3D-FLAIR sequence had higher SNR and CNR than previous 2D sequences. 14,15 Moreover, the 3D-FLAIR sequence has been shown useful in the diagnosis of mumps-related deafness and sudden sensorineural hearing loss, and for predicting the prognosis of patients with sudden sensorineural hearing loss, which is not usually demonstrated by the conventional MR imaging sequences. [16][17][18] This ability of the 3D-FLAIR sequence to find minute abnormalities mainly results from the high sensitivity of FLAIR imaging to subtle changes of longitudinal magnetization in the fluid space, which declines with the higher concentration of the contrast agent, different from T1-weighted images.…”
mentioning
confidence: 99%
“…In conclusion, previous studies (8,12) have shown the potential for using Cube to image the knee joint of 5T at an outside institution shows cyst within the CPN (asterisks). There is some cyst extension medially (arrowhead), but the complete course of the intraneural cyst is not demonstrated; specifically, the cyst within the articular branch cannot be seen.…”
Section: Discussionmentioning
confidence: 66%
“…Traditionally, two-dimensional (2D) fast spin echo (FSE) has been used to provide T2-weighted images in a reasonable scan time. 2D-FSE has limitations due to anisotropic voxels with relatively thick slices compared with in-plane resolution that leads to volume artifacts when applied in clinically feasible time periods, even when high field scanners are available (8). A three-dimensional (3D) acquisition is advantageous for reformatting, particularly with isotropic data, and leads to higher signal-to-noise ratio (SNR) which can be used to achieve higher resolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation